2005
DOI: 10.1038/nature03203
|View full text |Cite
|
Sign up to set email alerts
|

Role of the proto-oncogene Pokemon in cellular transformation and ARF repression

Abstract: Aberrant transcriptional repression through chromatin remodelling and histone deacetylation has been postulated to represent a driving force underlying tumorigenesis because histone deacetylase inhibitors have been found to be effective in cancer treatment. However, the molecular mechanisms by which transcriptional derepression would be linked to tumour suppression are poorly understood. Here we identify the transcriptional repressor Pokemon (encoded by the Zbtb7 gene) as a critical factor in oncogenesis. Mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
440
3
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 299 publications
(461 citation statements)
references
References 48 publications
11
440
3
7
Order By: Relevance
“…For example, ZBTB7 (Pokemon) has also been identified as a potent oncogene that can promote lymphomagenesis in mice and is up-regulated in human follicular lymphoma; moreover, like CBX7, ZBTB7 is a negative regulator of ARF (21). As shown here, CBX7 is often cooverexpressed with ZBTB7 in human follicular lymphomas, raising the possibility that these proteins act together to control expression from the INK4a/ARF locus.…”
Section: Discussionmentioning
confidence: 76%
“…For example, ZBTB7 (Pokemon) has also been identified as a potent oncogene that can promote lymphomagenesis in mice and is up-regulated in human follicular lymphoma; moreover, like CBX7, ZBTB7 is a negative regulator of ARF (21). As shown here, CBX7 is often cooverexpressed with ZBTB7 in human follicular lymphomas, raising the possibility that these proteins act together to control expression from the INK4a/ARF locus.…”
Section: Discussionmentioning
confidence: 76%
“…24 ZBTB7A/FBI-1/Pokemon, one of the POK (POZ and Kruppel-like zinc finger) families, directly binds the p19Arf promoter and can repress its activity, resulting in oncogenic transformation through inhibition of p53 activity. 30 Furthermore, loss of ZBTB7A/ Pokemon in mouse embryonic fibroblasts resulted in premature senescence and unresponsiveness to oncogenic stimuli, which was caused by aberrant upregulation of ARF. 31 We showed that the level of phosphorylated-ATM was increased during premature cellular senescence induced by PATZ1 knockdown (Figure 2f) and was decreased in cells overexpressing PATZ1 (Figure 3f).…”
Section: Discussionmentioning
confidence: 99%
“…These proteins have been demonstrated to participate in a wide variety of cellular functions including transcription regulation, cellular proliferation, apoptosis, cell morphology, ion channel assembly, and protein degradation through ubiquitination (1). A subset of BTB/POZ proteins have been implicated in human cancer, and they include BCL-6 (4, 5), PLZF (promyelocytic leukemia zinc finger) (4,6), leukemia/lymphoma-related factor (LRF)/Pokemon (7,8), HIC-1 (hypermethylated in cancer-1), and Kaiso (9,10). Among them, the BCL-6 gene is the best characterized oncogene.…”
mentioning
confidence: 99%